2020
DOI: 10.1021/acsapm.9b01202
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Solid-State 2,2′-Bithiophene Thin Film or Doped in Cellulose Paper Using DBD Plasma and Its Applications in Paper-Based Electronics

Abstract: We present a method to prepare a conductive paper hybrid based on the polymerization of bithiophene monomer directly from the solid state of 2,2′-bithiophene inside a sheet of standard letter paper using atmospheric plasma since both the monomers and some plasma species, such as radicals, can penetrate into the paper. Polymerization of a 2,2′-bithiophene in its solid form using plasma offers a simple and straightforward way to synthesize a conductive polymer. To understand the polymerization reaction in atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…BTh is the dimer of the thiophene unit that can be easily electropolymerized by potentiostatic, galvanostatic, or potentiodynamic techniques . Even if potential sweep techniques require longer reaction times to obtain well-attached polymer films compared to potentiostatic or galvanostatic measurements, this method is used due to the possibility to monitor the electrochemical properties of the growing polymer, along the polymerization process, allowing a detailed study of the electropolymerization kinetics. Hence, the electropolymerization of the monomer was carried out potentiodynamically by repetitive cycling of the electrode potential (between 0.0 and 1.2 V vs Ag/AgCl) in a solution containing 9.8 mM of the monomer and 0.1 M LiClO 4 in ACN:water (1:1 v/v), at a scan rate of 50 mV·s –1 (see SI, Figure S11). Under these conditions, an irreversible oxidation process on the surface of the ITO electrode in the ACN:water system was observed, showing in the first potentiodynamic cycle the typical trace-crossing effect observed during the electrochemical polymerization of π-conjugated systems .…”
Section: Resultsmentioning
confidence: 99%
“…BTh is the dimer of the thiophene unit that can be easily electropolymerized by potentiostatic, galvanostatic, or potentiodynamic techniques . Even if potential sweep techniques require longer reaction times to obtain well-attached polymer films compared to potentiostatic or galvanostatic measurements, this method is used due to the possibility to monitor the electrochemical properties of the growing polymer, along the polymerization process, allowing a detailed study of the electropolymerization kinetics. Hence, the electropolymerization of the monomer was carried out potentiodynamically by repetitive cycling of the electrode potential (between 0.0 and 1.2 V vs Ag/AgCl) in a solution containing 9.8 mM of the monomer and 0.1 M LiClO 4 in ACN:water (1:1 v/v), at a scan rate of 50 mV·s –1 (see SI, Figure S11). Under these conditions, an irreversible oxidation process on the surface of the ITO electrode in the ACN:water system was observed, showing in the first potentiodynamic cycle the typical trace-crossing effect observed during the electrochemical polymerization of π-conjugated systems .…”
Section: Resultsmentioning
confidence: 99%
“…The aminophenol-coated wafer was then treated with DBD in the atmospheric environment for 3 or 4 min until no further change was observed from on UV spectra. The DBD air plasma was generated using a setup reported previously [17]. Briefly, the size of the copper DBD electrode was 38 mm × 64 mm and it is covered with an 1-mm-thick glass slide.…”
Section: Experiments and Materialsmentioning
confidence: 99%
“…The frequency of the power supply was from 500 Hz to 1.5 kHz with a max amplitude of 20 kV magnitude. The voltage and frequency of the plasma set-up were 11.2 kV (R = 75 Ω) and 1 kHz, respectively, for all the experiments [17]. The plasma discharge gap was 5 mm and the temperature is at 25 • C.…”
Section: Experiments and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that nonthermal dielectric barrier discharge (DBD) plasma can be used to initiate the radical polymerization of solid-state 2,2 -bithiophene to form thin films [11]. We further demonstrated that DBD plasma could be used to polymerize the 2,2bithiophene inside of cellulose paper to make paper-based electronics.…”
Section: Introductionmentioning
confidence: 99%